2016
DOI: 10.1002/wsb.675
|View full text |Cite
|
Sign up to set email alerts
|

A long‐term evaluation of biopsy darts and DNA to estimate cougar density: An agency‐citizen science collaboration

Abstract: Accurately estimating cougar (Puma concolor) density is usually based on long‐term research consisting of intensive capture and Global Positioning System collaring efforts and may cost hundreds of thousands of dollars annually. Because wildlife agency budgets rarely accommodate this approach, most infer cougar density from published literature, rely on short‐term studies, or use hunter harvest data as a surrogate in their jurisdictions; all of which may limit accuracy and increase risk of management actions. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
(72 reference statements)
0
26
0
Order By: Relevance
“…Accounting for this is especially important for cougars because they are highly mobile and utilize large home ranges (Dickson and Beier ; females ~100 km 2 with some males >750 km 2 , unpublished data from this study). With the exception of Beausoleil et al () and Proffitt et al (), densities reported above were not corrected for spatial extent and therefore, could be biased high. Spatially explicit capture–recapture models, could also be used in a similar fashion to estimate density with our data, especially if telemetered animals were not available (Efford et al , Efford and Fewster ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Accounting for this is especially important for cougars because they are highly mobile and utilize large home ranges (Dickson and Beier ; females ~100 km 2 with some males >750 km 2 , unpublished data from this study). With the exception of Beausoleil et al () and Proffitt et al (), densities reported above were not corrected for spatial extent and therefore, could be biased high. Spatially explicit capture–recapture models, could also be used in a similar fashion to estimate density with our data, especially if telemetered animals were not available (Efford et al , Efford and Fewster ).…”
Section: Discussionmentioning
confidence: 94%
“…Two studies effectively estimated cougar density in Montana, USA, using bio‐darting to obtain tissue samples from cougars treed by hounds, and backtracking cougars during winter to obtain hair samples (Russell et al , Proffitt et al ). Additionally, Beausoleil et al () developed an effective sampling approach using a citizen scientist approach and bio‐darting to estimate cougar density at a game management unit scale in northeastern Washington, USA. This approach does account for detection probability, but is still field intensive.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cluster sampling coupled with spatially explicit capture‐recapture techniques has the potential to provide reliable estimates for a wide array of species and sampling situations. For example, SCR methods have been used in conjunction with area searches for mountain lions ( Felis concolor ; Beausoleil et al ), acoustic sampling for ovenbird ( Seiurus aurocapilla ; Dawson and Efford ), mark‐resight for raccoons ( Procyon lotor ; Sollmann et al ), camera traps for tigers ( Panthera tigris ; Gopalaswamy et al ), pellet collection for white‐tailed deer ( Odocoileus virginianus ; Goode et al ), and a variety of other methods and species. These and many other situations have the potential to benefit from cluster sampling designs when the sampling space is extensive.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the most common approaches for estimating mountain lion abundance tend to be too resource‐intensive to apply to large areas or annual surveys. Approaches such as mark‐recapture techniques (Lambert et al , Russell et al ), genetic mark‐recapture using DNA extracted from tissue, scat, or hair samples (Russell et al , Davidson et al , Beausoleil et al ), or identifying individuals from photographs captured by remote cameras (Kelly et al , Smythe , Negrões et al , Rosas‐Rosas and Bender ) have typically been applied to a limited geographic area or population. Recent advances in spatial mark‐resight models using camera trap data provide another means to estimate abundance (Rich et al , Murphy et al ) but still may be cost‐ and labor‐prohibitive for long‐term monitoring across a large landscape (Skalski et al , Clawson et al , Hatter ).…”
mentioning
confidence: 99%